Agglomeration, urbanization and employment growth in Ghana - Kerr, Andrew,McDougall, Bruce (World Bank Group, Africa Region, Office of the Chief Economist, 2019)
In this paper the impact of various agglomerative forces on employment growth in Ghanaian manufacturing is investigated, using data from two firm censuses, as well as population census and trade data. The study is the first to use nationally representative firm data that covers the formal and informal economy to investigate the impact of agglomerative forces on employment growth in an African economy. African economies are rapidly urbanizing, but this has not been accompanied by growth in manufacturing. A lack of agglomeration economies is one possible explanation for slow manufacturing growth and the attendant premature deindustrialization. The paper follows Combes (2000) in examining the importance of agglomeration economies on employment growth in Ghanaian manufacturing, finding that there is no evidence that population density is associated with faster employment growth. Other agglomeration economies do seem to play a role, although not always in the manner anticipated
10.1596/1813-9450-8946
Keywords: Graue Literatur; Ghana; Agglomeration economies; Employment Growth